The crystal-induced activation of NLRP3 inflammasomes in atherosclerosis - Tadayoshi Karasawa; Masafumi Takahashi (BMC, 2017)
Abstract Atherosclerosis is an inflammatory disease, which is accompanied by the deposition of cholesterol-rich lipids and the infiltration of macrophages. Other well-known features of atherosclerotic lesions include the deposition of cholesterol crystals and calcium phosphate crystals; however, their pathophysiological role remains unclear. Recent studies suggest that cholesterol crystals play a pivotal role in activation of NLRP3 inflammasomes, which regulate caspase-1 activation and the subsequent processing of IL-1β, in atherosclerotic lesions. NLRP3 inflammasomes are essential for the initiation of vascular inflammation during the progression of atherosclerosis. Therefore, the regulatory mechanisms of NLRP3 inflammasomes are regarded as potential targets for atherosclerosis treatment. Here, we review the current knowledge regarding the role of NLRP3 inflammasomes in the progression of atherosclerosis and the prospects for therapeutic approaches targeting NLRP3 inflammasomes.